ChatGPT, LaMDA, and the Hype Around Communicative AI: The Automation of Communication as a Field of Research in Media and Communication Studies - Andreas Hepp; Wiebke Loosen; Stephan Dreyer; Juliane Jarke; Sigrid Kannengießer; Christian Katzenbach; Rainer Malaka; Michaela Pfadenhauer; Cornelius Puschmann; Wolfgang Schulz (Human-Machine Communication Journal, 2023)
The aim of this article is to more precisely define the field of research on the automation of communication, which is still only vaguely discernible. The central thesis argues that to be able to fully grasp the transformation of the media environment associated with the automation of communication, our view must be broadened from a preoccupation with direct interactions between humans and machines to societal communication. This more widely targeted question asks how the dynamics of societal communication change when communicative artificial intelligence—in short: communicative AI—is integrated into aspects of societal communication. To this end, we recommend an approach that follows the tradition of figurational sociology.